2012
DOI: 10.1124/mol.112.078907
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) Polymerase 1 Modulates the Lethality of CHK1 Inhibitors in Mammary Tumors

Abstract: The present studies sought to define whether checkpoint kinase 1 (CHK1) inhibitors and poly(ADP-ribose) polymerase 1 (PARP1) inhibitors interact in vitro and in vivo to kill breast cancer cells. PARP1 and CHK1 inhibitors interacted to kill estrogen receptor (ER)ϩ, ERϩ fulvestrant-resistant, HER2ϩ, or triple-negative mammary carcinoma cells in a manner that was not apparently affected by phosphatase and tensin homolog deleted on chromosome 10 functional status. Expression of dominant-negative CHK1 enhanced and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 47 publications
(48 reference statements)
1
25
1
Order By: Relevance
“…Fourth, we found that profound Chk1 depletion did not affect ABT-888 sensitivity. This result contrasts with studies showing that Chk1 depletion or inhibition sensitizes tumor cells to PARP inhibition in other experimental systems (McCabe et al, 2006;Mitchell et al, 2010;Tang et al, 2012), thus suggesting that the requirement for Chk1 in PARP-inhibited cells may vary significantly among tumor cell types. Finally, the observation that Chk1 depletion did not influence FdUrd toxicity was unexpected given that Chk1 has been implicated in the regulation of RAD51 and HR (Sørensen et al, 2005), which we showed markedly protect cells from FdUrd.…”
Section: Downloaded Fromcontrasting
confidence: 54%
“…Fourth, we found that profound Chk1 depletion did not affect ABT-888 sensitivity. This result contrasts with studies showing that Chk1 depletion or inhibition sensitizes tumor cells to PARP inhibition in other experimental systems (McCabe et al, 2006;Mitchell et al, 2010;Tang et al, 2012), thus suggesting that the requirement for Chk1 in PARP-inhibited cells may vary significantly among tumor cell types. Finally, the observation that Chk1 depletion did not influence FdUrd toxicity was unexpected given that Chk1 has been implicated in the regulation of RAD51 and HR (Sørensen et al, 2005), which we showed markedly protect cells from FdUrd.…”
Section: Downloaded Fromcontrasting
confidence: 54%
“…The CHK1 inhibitor LY2603618 was purchased from Selleckchem. 12,13 penicillin, 100 μg/ml streptomycin and 250 μg/ml amphotericin B) and trypsin-EDTA were purchased from Invitrogen. All the primary antibodies used in the present study were purchased from Cell Signaling Technology.…”
Section: Resultsmentioning
confidence: 99%
“…12,13,30 The present studies were performed to determine in further detail the biology by which PARP1 inhibitors interact with CHK1 inhibitors to promote breast cancer cell killing. Multiple PARP1 and CHK1 inhibitors interacted in a greater than additive fashion to kill mammary tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence implicating a role for Chk1 in the cell‐cycle and DNA replication in the absence of exogenous DNA damage suggests combining a Chk1 inhibitor with alternative, molecularly targeted therapeutic agents may be a rational therapeutic option. Synergism with Chk1 inhibitors (UCN‐01, LY2603618 and PF‐477736) or a pan Chk1/Chk2 inhibitor (AZD7762) has so far been observed with MEK inhibitors in glioblastoma (Tang et al., 2012a) and cytokinetically quiescent multiple myeloma (Pei et al., 2011); with PARP inhibitors in breast cancer (Mitchell et al., 2010; Shibata et al., 2011; Tang et al., 2012a); with Src family kinase inhibitors in glioblastoma (Tang et al., 2012b), multiple myeloma (Dai et al., 2008, 2011) and breast cancer (Mitchell et al., 2011); with farnesyl transferase inhibitors in leukaemia and myeloma (Dai et al., 2005); and with the mTOR inhibitor rapamycin in leukaemia (Hahn et al., 2005). Chk1 inhibitors have demonstrated single agent activity in cancers harbouring defects in DNA repair pathways or with high levels of replicative stress including neuroblastoma (Cole et al., 2011), melanoma (Brooks et al., 2013), leukaemia and lymphoma (Bryant et al., 2014b; Ferrao et al., 2012; Murga et al., 2011), breast cancer (Bryant et al., 2014a; Shibata et al., 2011), and cell lines defective in components of the Fanconi's anaemia DNA repair pathway (Chen et al., 2009).…”
Section: Introductionmentioning
confidence: 99%